“Garnierite” in weathering crust of ultramafic blocks from Cao Bang area, north Viet Nam - Dang, Pham Thanh; Xuan, Pham Tich; Pho, Nguyen Van (Vietnam Journal of Earth Sciences, 2020)
"Garnierite" is an important group of ore minerals in the supergene nickel deposits. Garnierite group minerals are Ni-bearing hydrous magnesium silicate formed due to the lateritic weathering of ultramafic rocks under humid tropical conditions. In the weathering crust on ultra-mafic blocks Ha Tri and Phan Thanh (Cao Bang province), garnierite group minerals have been found in the saprolite zone or as a coating on the surface of the fissures. Analytical results show that garnierite consists of a mixture of three solid solutions: (i) serpentine-like - 7Ao (lizardite-nepouite), (ii) talc-like - 10 Ao (pimelite-willemseite) and (iii) chlorite-like - 14 Ao (clinochlore-minite). EPMA analysis shows that garnierite in Cao Bang area is characterized by high Ni content (25.50-40.06%), low Fe content (0.09-0.9%) and almost no Al (<0.02%), similar to garnierite in the famous nickel mines in New Caledonia, Dominican Republic, etc... Notable, Ni and Mg contents in garnierite show a clear negative correlation, indicating the replacement for each other in the phases. Under the scanning electron microscope (SEM), garnierite has a raspberry shape forming continuous zones covering the unfinished weathered rock surface. These zones represent different stages of garnierite formation. The results of the study allow proposing a model of garnierite formation in the lateritic weathering zone in ultramafic blocks in the Cao Bang area.